About Inca military history - Espinoza Soriano, Waldemar (1980)
The history of the Inca civilization has proven to be one of the most attractive subjects for social scientists and scholars in general, from Peru and from all parts of the world, and since the sixteenth century when the Spanish intervened and destructured it. . Four hundred and fifty years have passed and the facts show and persuade that this situation will continue the same for many more decades. The foundations that preserve the inalterability of this extraordinary interest have been and are economic, social, political, legal and ideological structures and superstructures, which made possible the emergence and operation of an imposing imperial-type state apparatus, but without breaking down or exterminating thousands of of village communities, called ayllus, whose collective ownership of their lands and reciprocal help persisted controlled, directed and protected by a minority of princes residing in Cusco.